An Assessment of Patient’s Awareness of Radiation Exposure to Common Diagnostic Imaging Procedures in Low Socioeconomic Regions of Nepal - Ghimire, Prasanna; Koirala, Dwight; Singh, Bhuvaneswor Prasad (Nepalese Journal of Radiology, 2018)
Introduction: Radiological investigations form a cornerstone in the management of patients. Patient might me unware of the radiation exposure. The aim of this study is to assess patient’s knowledge of radiation exposure to common diagnostic imaging procedures. Methods: A cross-sectional study was conducted and questionnaire used to collect data from 216 patients who had undergone radiological investigations. Results: Among 216 patients, there were 112 (51.85 %) females and 104 (48.15 %) males. The age of the patients ranged from 12 years to 66 years. Only 65 patients (30.1 %) were aware of the radiation hazards. Neoplasm was the most common side effect chosen by 60 patients. 44 patients were informed of radiation hazards with only 17 patients however informed by the referring doctor. Patients having undergone radiological procedure previously were more aware of radiation hazards (21 patients out of 26 patients). Conclusion: This study showed dearth of knowledge and awareness regarding radiation hazards amongst general public which mandates education.